2015
DOI: 10.1177/2168479014543699
|View full text |Cite
|
Sign up to set email alerts
|

The Wider Use of Fixed-Dose Combinations Emphasizes the Need for a Global Approach to Regulatory Guideline Development

Abstract: A fixed-dose combination (FDC) is a drug product in which two or more separate drug components (active pharmaceutical ingredients) are combined in a single-dosage form. Interest in developing FDCs is increasing in a range of diseases. This project investigated the regulatory environment for FDCs in the EU and US. A review of the FDC guidelines set forth by the EMA, FDA, and ICH, followed by interviews of key informants in industry, identified 5 main industry concerns related to development of FDCs. These conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…6 However, it was found that there are several gaps and a lack of harmonization of FDC regulations between the US Food and Drug Administration (FDA) and the EMA. 7 In the US, a fixed-dose combination drug is defined as “a drug product in which two or more separate drug components are combined in a single dosage form,” which is similar to the EMA’s definition, but the definition of a second term, the combination product , is a distinct and unique concept of the US FDA, and it is defined as a product composed of two or more components (ie, drug/device, biologic/device, drug/biologic, or drug/device/biologic). 7 –9 In the US, there are some regulations concerning the development of FDCs, but specific guidance that directs the required clinical programs of the FDCs is not currently available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, it was found that there are several gaps and a lack of harmonization of FDC regulations between the US Food and Drug Administration (FDA) and the EMA. 7 In the US, a fixed-dose combination drug is defined as “a drug product in which two or more separate drug components are combined in a single dosage form,” which is similar to the EMA’s definition, but the definition of a second term, the combination product , is a distinct and unique concept of the US FDA, and it is defined as a product composed of two or more components (ie, drug/device, biologic/device, drug/biologic, or drug/device/biologic). 7 –9 In the US, there are some regulations concerning the development of FDCs, but specific guidance that directs the required clinical programs of the FDCs is not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the US, a fixed-dose combination drug is defined as “a drug product in which two or more separate drug components are combined in a single dosage form,” which is similar to the EMA’s definition, but the definition of a second term, the combination product , is a distinct and unique concept of the US FDA, and it is defined as a product composed of two or more components (ie, drug/device, biologic/device, drug/biologic, or drug/device/biologic). 7 –9 In the US, there are some regulations concerning the development of FDCs, but specific guidance that directs the required clinical programs of the FDCs is not currently available. 8,10 –12 Therefore, if a pharmaceutical company wishes to develop a unique FDC product for the US market, the company should also refer to applicable precedent cases and other health agencies’ regulations to prepare the clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the EMA guidelines are written and directed for combinations of 2 or more drugs that are already approved for the indication of the FDC or where 1 substance is a new active substance. 14 Yet, the FDA also focuses on combinations containing devices. 14 This article focuses on only the perspective from EMA, although for future studies, it may be of interest to analyze the FDCs being authorized by the FDA.…”
Section: Introductionmentioning
confidence: 99%
“…14 Yet, the FDA also focuses on combinations containing devices. 14 This article focuses on only the perspective from EMA, although for future studies, it may be of interest to analyze the FDCs being authorized by the FDA. Gautam et al 14 surveyed European regulators concerning EMA and FDC guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation